Logging Evaluation of Mixed-sediments Reservoirs of the Lower Cambrian Canglangpu Formation in Penglai Gas Area, Central Sichuan Basin - WANG Haiqing; WANG Zeyu; LAI Qiang; LI Shurong; WU Yuyu; ZHANG Mingyong; WANG Yaqing (Cejing jishu)
The Canglangpu formation of Lower Cambrian, Penglai gas area, north slope of central Sichuan paleo-uplift is a new formation which has achieved breakthrough in oil and gas exploration in recent years. In the first member of Canglangpu formation, carbonate sediments and siliciclastic detritus present the depositional pattern of vertical alternation or horizontal succession, it is difficult to accurately calculate the contents of various minerals because of the variety of rock types. The evaluation of mixed-sediments reservoirs is mainly based on the accurate calculation of mineral composition, physical parameters and the evaluation of reservoir effectiveness. From an overall perspective, the regularity of porosity to permeability is poor, the electrical differentiation of gas abundance is fuzzy, so the traditional parameter calculation model is not applicable, and it is urgent to study an effective logging evaluation method. Using the core analysis data such as cast thin section, XRD, physical property, logging data and gas testing data, the paper studied a systematic evaluation method for calculating the mineral component by dimensionality reduction, neural network analysis and element content to mineral content inversion method, calculating porosity by variable matrix parameters on the basis of tri-porosity logging curves, calculating permeability by lithologic subdivision model, and quantitative evaluation of reservoir property, connectivity and permeability by array acoustic wave combined with electrical imaging logging, then determined the lower limit of effective reservoir and the classification standard of reservoir. Results show that, the dimensionality reduction method and other methods have solved the problem of calculating the composition and content of more than four kinds of minerals, and the calculation results are highly consistent with the Litho Scanner logging data, the porosity calculated by variable matrix parameters on the basis of tri-porosity logging curves and the permeability calculated by subdivision model are in good agreement with those from core analysis, the electrical imaging logging combined with acoustic remote detection and acoustic velocity tomography has a good application effect to judge the pore space type characteristics and reservoir effectiveness. The comprehensive method can effectively evaluate the diamictic carbonate reservoirs in Canglangpu formation.